Type 2 Autoimmune Pancreatitis: A Challenge in the Differential Diagnosis of a Pancreatic Mass - Martins, C. (2017)
Autoimmune pancreatitis is a rare entity of unknown etiology that can mimic pancreatic cancer and whose diagnosis involves clinical, serological, imagiological, and histological findings. There are two types of autoimmune pancreatitis: type 1, in which the pancreas is involved as one part of a systemic immunoglobulin G4-related disease, and type 2, generally without immunoglobulin G4-positive cells and without systemic involvement.